Pollination Is Sufficient, Even with Low Bee Diversity, in Pumpkin and Winter Squash Fields - Kimberly A. Stoner (Agronomy, 2020)
Pumpkins and winter squash require insect pollination to set fruit, but only three bee species are important pollinators of these crops in the Northeastern US. To determine if natural levels of pollen deposition are sufficient for full fruit production, open pollination was measured by counting pollen grains on stigmas, and open pollination was compared to supplemental hand pollination for fruit set, fruit size, and seed number. A threshold of 2300 pollen grains per stigma was sufficient for full pollination and fruit production. This threshold was met in 79 out of 80 combinations of site and sample date over four years on farms across Connecticut with a wide range of field sizes and pest management practices. Along with stigma collection, bees per flower were counted hourly on 100 flowers along a transect. Counts of bumble bees on female flowers were more closely related to the amount of pollen deposited than counts of bees on all flowers or counts of honey bees or squash bees on female flowers. There was tremendous variation in abundance of the three bee species on female flowers across farms within a year and even among years on a single farm.